A systematic review of segmental vs subtotal colectomy and subtotal colectomy vs total proctocolectomy for colonic Crohn's disease. (2nd August 2017) - Angriman, I.; Pirozzolo, G.; Bardini, R.; Cavallin, F.; Castoro, C.; Scarpa, M.
Abstract: Aim: Surgical management of colonic Crohn's disease (CD) is still unclear because different procedures can be adopted. The choice of operation is dependent on the involvement of colonic disease but the advantages and disadvantages of the extent of resection are still debated. Method: The aim of the present study was to evaluate the differences in short‐term and long‐term outcomes of adult patients with colonic CD who underwent either subtotal colectomy and ileorectal anastomosis (STC) or segmental colectomy (SC) or total proctocolectomy and end ileostomy (TPC). Studies published between 1984 and 2012 including comparisons of STC vs SC and of STC vs TPC were selected. The study end‐points were overall and surgical recurrence, postoperative morbidity and incidence of permanent stoma. Fixed effect models were used to evaluate the study outcomes. Results: Eleven studies, consisting of a total of 1436 patients (510 STC, 500 SC and 426 TPC), were included. Analysis of the data showed no significant difference between STC and SC in terms of overall and surgical recurrence of CD. In contrast, STC showed a higher risk of overall and surgical recurrence of CD than TPC (OR 3.53, 95% CI 2.45–5.10, P < 0.0001; OR 3.52, 95% CI 2.27–5.44, P < 0.0001, respectively). SC had a higher risk of postoperative complications compared to STC, and STC had a lower risk of complications than TPC (OR 2.84, 95% CI 1.16–6.96, P < 0.02; OR 0.19, 95% CI 0.09–0.38, P < 0.0001, respectively). SC resulted in a lower risk of permanent stoma than STC (OR 0.52, 95% CI 0.35–0.77). Conclusion: All three procedures were equally effective as treatment options for colonic CD and the choice of operation remains intrinsically dependent on the extent of colonic disease. However, patients in the TPC group showed a lower recurrence risk than those in the STC group. Moreover, SC had a higher risk of postoperative complications but a lower risk of permanent stoma. These data should be taken into account when deciding surgical strategies and when informing patients about postoperative risks.